(untitled) - McElwee, Pamela (New York, 1999)
The review is presented in two volumes. The first volume is a substantive discussion of the region as drawn the literature. It is intended only as a guide to the literature and does not preten to be comprehensive in any of its sections,...
Keywords: Ecology and environment,Agriculture systems,Environmental protection; Lower Mekong basin and delta,Lower Mekong basin and delta,Lower Mekong basin and delta